Rich p-type-doping phenomena in boron-substituted silicene systems - Hai Duong Pham; Wu-Pei Su; Thi Dieu Hien Nguyen; Ngoc Thanh Thuy Tran; Ming-Fa Lin (Royal Society Open Science, 2020)
The essential properties of monolayer silicene greatly enriched by boron substitutions are thoroughly explored through first-principles calculations. Delicate analyses are conducted on the highly non-uniform Moire superlattices, atom-dominated band structures, charge density distributions and atom- and orbital-decomposed van Hove singularities. The hybridized 2pz–3pz and [2s, 2px, 2py]–[3s, 3px, 3py] bondings, with orthogonal relations, are obtained from the developed theoretical framework. The red-shifted Fermi level and the modified Dirac cones/π bands/σ bands are clearly identified under various concentrations and configurations of boron-guest atoms. Our results demonstrate that the charge transfer leads to the non-uniform chemical environment that creates diverse electronic properties.